OVERVIEW OF MODERN APPROACHES TO THE FORMATION AND DISTRIBUTION OF THE COMPANY'S MATERIAL AND INFORMATIONAL RESOURCES - ABUSHOV, Teymur (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is a general overview of approaches to the management of material resources of a manufacturing enterprise. Approaches to defining the concepts of "material resources" and "material resources of the enterprise" and the composition of the material resources of the enterprise are analyzed. It is agreed that material resources include raw materials, main and auxiliary materials, component products, fuel, work in progress and production waste. Features of material resources as an object of management at the enterprise are highlighted and include material form, usage in production process, transfer of their value to the value of produced products. An analysis of individual approaches to material resource management is carried out, in particular, integral, functional, logistic and reengineering approaches.An improved list of material resource management tasks within the framework of individual functional divisions of the enterprise is proposed. The functional divisions include economic and planning, marketing, procurement, accounting, legal department, production, information department. Areas of activity in the field of management of material resources of an industrial enterprise within the framework of separate management functions are suggested and grouped, including activities aimed at coordinating other management functions. In particular, the market factor is the basis of planning, and the need to implement an information system for the management of material resources and ensure its smooth operation to ensure the coordination of management activities for the management of material resources is emphasized.The place and role of the company's information  system is determined as such that helps unification of data sources, serves as information base for management decisions, allows to improve the process of management of material resources, ensures higher level of control and risks prevention, reduces the risk of human factor. Proposals for further scientific research were formed.
Keywords: enterprise resources; enterprise material resources; enterprise resource management; enterprise information resources; industrial enterprise management